Enhancing academic motivation and career awareness: a digital TPB-based counseling intervention for high school students - Mulyani Mulyani (Jurnal Konseling dan Pendidikan, 2025)
Digital transformation presents novel opportunities within education; however, persistently low learning motivation and underdeveloped career awareness among students continue to pose significant challenges. This study investigates the efficacy of an integrative counseling model grounded in the Theory of Planned Behavior (TPB) for enhancing learning motivation and career awareness among senior high school students. A randomized controlled trial (RCT) employing a pretest–posttest control group design with a one-month follow-up was implemented. From an initial pool of 78 screened students, 60 who met the inclusion criteria were randomly allocated to either an intervention group (n = 30) or a control group (n = 30). The intervention group received eight structured digital counseling sessions delivered via Zoom and WhatsApp, facilitated by certified school counselors. The session content targeted the core TPB constructs: attitudes, subjective norms, perceived behavioral control, and behavioral intentions. Intervention fidelity was ensured through the use of session checklists and weekly supervision. Baseline demographic data confirmed group equivalence (mean age = 16.4 years; 55% female; all p > .05). The Motivated Strategies for Learning Questionnaire (MSLQ) and the Career Awareness Scale were administered to measure outcomes. Repeated Measures Analysis of Variance (ANOVA) yielded a significant group × time interaction effect for both learning motivation (F(2, 116) = 8.72, p < .001, η² = 0.13) and career awareness (F(2, 116) = 9.15, p < .001, η² = 0.14). No adverse events were reported. The results substantiate the effectiveness of the TPB-based digital counseling intervention, although limitations such as the single-site sample and brief follow-up period warrant caution regarding the generalizability of the findings.